2000
DOI: 10.1029/1999jd901064
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport and weakening of atmospheric stability induced by mesoscale flows

Abstract: Abstract. We present an analytical evaluation and interpretation on how diabatic heating of the convective boundary layer (CBL) is transported upward into the midtroposphere by mesoscale flows, and how the air mixes with the environment and therefore weakens the atmospheric static stability. The thermodynamic imprint on the free atmosphere due to the irreversible processes such as mixing, dissipation, and diffusion, associated with the mesoscale flow, is more clearly shown when the forcing is periodic in time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The energy fluxes help determine the thermodynamics of the PBL (Hong and Pan 2000;Barros and Hwu 2002), as indicated by a number of stability indices [e.g., lifted index (LI), "cap strength," CAPE; see Peppler and Lamb 1989;Eltahir and Pal 1996;Schreiber et al 1996;Doran and Zhong 2000;Donner and Phillips 2003]. Moreover, large height differences between crops and trees aerodynamically influence PBL characteristics (Banta and White 2003), potentially inducing mesoscale vertical circulations across LULC boundaries that promote convection, or nonclassical mesoscale circulations (NCMCs) (e.g., Segal et al 1989;Travis 1997;Dalu et al 2000;Carleton et al 2001). Experiments with regional atmospheric models for the central United States suggest a preferred horizontal length scale of 10-20 km (Baidya Roy et al 2003) over which the energy and moisture contrasts associated with land surface heterogeneities become organized into NCMCs (Segal and Arritt 1992), although the relatively few ob-servational studies undertaken have not unambiguously detected these circulations (Hubbe et al 1997).…”
Section: B Backgroundmentioning
confidence: 99%
“…The energy fluxes help determine the thermodynamics of the PBL (Hong and Pan 2000;Barros and Hwu 2002), as indicated by a number of stability indices [e.g., lifted index (LI), "cap strength," CAPE; see Peppler and Lamb 1989;Eltahir and Pal 1996;Schreiber et al 1996;Doran and Zhong 2000;Donner and Phillips 2003]. Moreover, large height differences between crops and trees aerodynamically influence PBL characteristics (Banta and White 2003), potentially inducing mesoscale vertical circulations across LULC boundaries that promote convection, or nonclassical mesoscale circulations (NCMCs) (e.g., Segal et al 1989;Travis 1997;Dalu et al 2000;Carleton et al 2001). Experiments with regional atmospheric models for the central United States suggest a preferred horizontal length scale of 10-20 km (Baidya Roy et al 2003) over which the energy and moisture contrasts associated with land surface heterogeneities become organized into NCMCs (Segal and Arritt 1992), although the relatively few ob-servational studies undertaken have not unambiguously detected these circulations (Hubbe et al 1997).…”
Section: B Backgroundmentioning
confidence: 99%
“…2, could be produced, thus possibly influencing the location and intensity of precipitation when the next synoptic-scale disturbance entered the domain. Dalu et al (2000) have shown that, even disregarding water vapor transport, persistent mesoscale flow should have an impact on atmospheric stability that is significant compared to boundary layer turbulence and diabatic heating. Since soil wetness is a major control on the partitioning of surface fluxes into sensible and latent heat, these impacts on precipitation might also systematically alter the surface heterogeneity that is the driving force for the landscape-generated mesoscale circulations, thus resulting in positive or negative feedbacks.…”
Section: Referencesmentioning
confidence: 99%
“…Some thermally-generated mesoscale circulations are due to horizontal inhomogeneities in ground wetness, vegetation cover, snow cover, cloud cover as studied by many authors, e.g. [8,[10][11][12][13]. In addition there are also anthropogenic modifications of soil and vegetation, such as irrigated or non-irrigated fields, crops at different stages of growth, inhabited areas, and so on [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%